Repercussão geral em matéria criminal - Bortolon, Nícolas Bortolotti (2018)
The Constitutional Amendment n. 45, dated December 30, 2004, included, among many other changes in the constitutional text, the insertion of a §3 in article 102, which provided that the applicant should demonstrate, in the reasons for his extraordinary appeal, the general repercussion of constitutional matters discussed in the case, so that the brazilian Federal Supreme Court may examine its admission, and may only deny it by the manifestation of two-thirds of its members. A filter of access to the jurisdiction of our Supreme Court was created, regarding the diffuse control of constitutionality, succinctly denominated of "general repercussion". In the study and practice of the Criminal Juridical Sciences, questions arose about the applicability of such an institute to the extraordinary recourse of the criminal process, given the public, inavailable and fundamental nature of the rights involved in this area, in theory, possessing relevance and transcendence in all cases. It occurs that the brazilian Federal Supreme Court, charged with defining the semantic limits of the general repercussion, at the very beginning of the institute, pointed out that the extraordinary criminal appeal also submitted to the provisions of art. 102, §3, of the CF and its infraconstitutional rule. This gave rise to certain doubts, then, of which constitutional questions in criminal and criminal procedural matters would have relevance and transcendence and, more than that, those that would not possess such attributes. As the definition of these criteria was relegated by the reforming constitutional legislator and by the ordinary legislator to the STF itself, the Court's jurisprudence is the main source from which the general repercussion in criminal matters can be extracted and the parameters established by our Supreme Court for the definition of what is or is not relevant and transcendent in this section of the Law and, with that, also confirm or invalidate the thesis initially arising from the institution of said recursional filter in the sense that all criminal issues of a kind have an inevitable general repercussion.